A Conceptual Model of Multiple-Measures Assessment for Evaluating Indonesian Teachers: A Literature Review - Mahurni (Samudra Publisher, 2026)
Teacher quality remains a decisive factor in determining students’ academic achievement and the overall effectiveness of educational systems. In Indonesia, despite the large-scale implementation of the teacher certification program, concerns persist regarding its limited impact on improving instructional performance. This situation highlights the need for a more comprehensive and accountable evaluation framework. This study aims to systematically review and synthesize existing scholarly literature on Multiple-Measures Evaluation in educational settings, examine how this approach contributes to improving teachers’ instructional performance in Indonesia, and identify the measurement models and administrative approaches that support accountability and professional development. Employing a literature review design, this research analyzed 60 selected academic sources retrieved from major educational databases. The findings reveal that integrating multiple evaluation measures, such as Value-Added Measures, classroom observation, student and parent surveys, and portfolio assessment, provides stronger reliability, construct validity, and decision validity compared to single-measure systems. Furthermore, the literature suggests that a conjunctive administrative approach is more suitable for ensuring balanced accountability within the Indonesian educational context. Although each measurement model has inherent limitations, their combined implementation offers a more comprehensive and credible framework for evaluating teaching performance. The study concludes that a structured Multiple-Measures Evaluation system has significant potential to enhance instructional effectiveness, strengthen accountability, and foster sustainable professional development among teachers in Indonesia.